Buddhist idea of ‘upaya-prajnya’ in the context of development strategy of modern society - Erendzhenova, Yulia Yu.; Badmaev, Valeriy N.; Ulanov, Mergen S. (The New Research of Tuva, 2025)
The article evaluates the effectiveness of the ‘upaya-prajna’ concept, one of the fundamental categories of the Tantric Buddhist tradition, as a strategy for the spiritual development of modern society. The relevance of the study is determined by the need to develop strategies that prioritize universal human interests and the awareness of the world's integrity in the spirit of “new humanism”. The methodology of intercultural philosophy makes it possible to turn to Buddhist culture as a source of alternative strategies.It has been established that the essence of the ‘upaya-prajna’ concept lies in the union of method (bodhicitta) and wisdom (the realization of shunyata). In the Tibetan tradition, ‘upaya-prajna’ is embodied in the tantric practice of the All-Encompassing Yoga.In relation to the strategy for social development, the concept of ‘upaya-prajna’ can be interpreted as the unity of the ethical (method) and the rational (wisdom). It is noted that the principles of rationality and ethics can and should be complementary elements, which aligns with N. Bohr’s principle of complementarity. This principle can be interpreted as the existence of a specific complementarity between rationality and morality, reason and heart, wisdom and compassion.The article presents the opinions of leaders of Buddhist organizations from Tibet, Bhutan, and Russia, affiliated with the Tibetan tradition, whose interviews were conducted in 2023. The interview materials revealed that they propose a balanced combination of method and wisdom as a solution to global challenges facing humanity.
Keywords: Buddhism; global problem; globalization; principle of complementarity; intercultural philosophy; Buddhist world; Buddhist strategy; upaya-prajna; method-wisdom